Facilitating Integrated Perinatal Care for Families Affected by Substance Use. Issue 1 (8th January 2023) - Schmidt, Christina N.; Patel, Devika; Alpers, Benjamin S.; Spaulding, Marcy; Ocegueda, Liliana; Thomas, Melanie; Sammann, Amanda; Briscoe, Heather
Abstract : Families of newborns are frequently referred to child protection systems because of parental substance use, yet many families face barriers to accessing prenatal care and substance use treatment services. Although federal legislation requires states to develop Plans of Safe Care to address families' health and substance use treatment needs, few have developed comprehensive and systematic approaches to provide perinatal support to parents and infants. In this commentary, we describe the development and initial testing of a Plan of Safe Care that engages patients and their providers in perinatal care coordination. Developed out of an in-depth analysis of current care workflows at an urban safety net health system, the Plan of Safe Care facilitates conversations with clients around delivery planning and aligns resources to support families with substance use disorders.